The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fphys.2020.00097
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia During Exercise: Impact on Adenosine Plasma Levels and Hemodynamic Data

Abstract: Introduction: Adenosine is an ATP derivative that is strongly implicated in the cardiovascular adaptive response to exercise. In this study, we hypothesized that during exercise the hyperemia, commonly observed during exercise in air, was counteracted by the downregulation of the adenosinergic pathway during hyperoxic exposure.Methods: Ten healthy volunteers performed two randomized sessions including gas exposure (Medical air or Oxygen) at rest and during exercise performed at 40% of maximal intensity, accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The vasoconstrictor effect of the decrease in APL was therefore implicated in hemodynamic differences and better tolerance to orthostatic stress during hyperoxic exposure [ 5 ]. These findings were supported by another study in healthy volunteers reporting that breathing pure oxygen at atmospheric pressure can increase peripheral vascular resistance associated with a decrease in APLs compared with the same session in air [ 48 ]. The differences remained significant between the two sessions when a low-intensity exercise was added to each experimental condition.…”
Section: Hyperoxiasupporting
confidence: 59%
See 1 more Smart Citation
“…The vasoconstrictor effect of the decrease in APL was therefore implicated in hemodynamic differences and better tolerance to orthostatic stress during hyperoxic exposure [ 5 ]. These findings were supported by another study in healthy volunteers reporting that breathing pure oxygen at atmospheric pressure can increase peripheral vascular resistance associated with a decrease in APLs compared with the same session in air [ 48 ]. The differences remained significant between the two sessions when a low-intensity exercise was added to each experimental condition.…”
Section: Hyperoxiasupporting
confidence: 59%
“…The differences remained significant between the two sessions when a low-intensity exercise was added to each experimental condition. Meanwhile, hyperoxia did not suppress the increase in APL and the decrease in peripheral vascular resistance commonly recorded during exercise compared with resting reference [ 48 ]. In addition to various factors such as nitric oxide, prostacyclin (PGI2), and endothelium-derived hyperpolarizing factor [ 49 ], adenosine may be another important contributor involved in muscle hyperemia during exercise [ 50 ].…”
Section: Hyperoxiamentioning
confidence: 99%
“…Adenosine is an inter-cellular modulator that signals altered cellular activity and metabolic stress within a tissue by activating adenosine receptors [ 1 ]. Acute exercise increases adenosine levels in human blood [ 2 , 3 ] and the rat brain [ 4 ]. Accordingly, adenosine contributes to exercise-induced vasodilation [ 5 ] and also causes drowsiness and tiredness at rest, being a candidate molecule to signal exercise fatigue [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is compelling evidence that patients exposed to hyperoxia have an increased risk of both short- and long-term mortality [ 17 , 18 ]. This risk is related to both the extent and the duration of hyperoxia patients were exposed to, although recent in-vivo studies have demonstrated that even a short exposure to supra-physiological oxygen levels may result in haemodynamic changes (reduction in cardiac output and an increase in vascular resistance for example) that may contribute to a worse outcome [ 19 ].…”
Section: Discussionmentioning
confidence: 99%